LGBTQ+ status and sex of record in Veterans with post-traumatic stress disorder: demographics, comorbidities, and outpatient encounters - Terri Elizabeth Workman; Terri Elizabeth Workman; Joseph L. Goulet; Joseph L. Goulet; Cynthia A. Brandt; Cynthia A. Brandt; Melissa Skanderson; Melissa Skanderson; John O’Leary; John O’Leary; Kirsha S. Gordon; Kirsha S. Gordon; et al. (Frontiers in Public Health)
ObjectivesThis study aims to analyze differences between lesbian, gay, bisexual, transgender, and queer (LGBTQ+) and non-LGBTQ+ Veterans with post-traumatic stress disorder (PTSD) in terms of demographics, comorbidities, and medical care usage, including differences by sex of record, including separate analyses for transgender and non-transgender Veterans.MethodsChi-square, t-test, ANOVA Welch one-way testing, and absolute standardized difference analyses were conducted on a cohort of 277,539 Veterans diagnosed with PTSD.ResultsThe study found significant differences, particularly concerning positive LGBTQ+ status and sex of record. There were significant differences found in age, marital status, and medical care usage, as well as pain, mental health, and substance use disorder diagnoses. Differences in having experienced military sexual trauma, crime, or maltreatment were especially significant, with increased percentages among LGBTQ+ individuals, and sex of record females. In separate analyses, there were similar differences among transgender and non-transgender Veterans, with similar increased risks for sex of record females.ConclusionOur findings suggest an intersectionality of LGBTQ+ status and sex of record in the context of PTSD. These findings may help guide future research, policy, and interventions.